CHOROID PLEXUS CARCINOMA AND CHOROID PLEXUS PAPILLOMA; RARE CASES - Şule Çalışkan Kamış; Begül Yağcı; Barbaros Şahin Karagün (Hematology, Transfusion and Cell Therapy)
Case Report: Choroid plexus carcinoma (CPC) is a rare and aggressive intracranial neoplasm, constituting 1–4% of all brain tumors and approximately 40% of choroid plexus tumors. Classified as a WHO Grade III malignancy, CPC is characterized by a poor prognosis, with reported 5-year survival rates around 40%. In contrast, choroid plexus papilloma (CPP), classified as a WHO Grade I tumor, is a benign and slow-growing lesion originating from the epithelial cells of the choroid plexus.This report presents four cases of choroid plexus tumors: two diagnosed as choroid plexus carcinoma (WHO Grade III) and two as choroid plexus papillomas (WHO Grade I). The CPP cases were managed with observation and followed up without active treatment. Among the CPC cases, a 3-year-old patient received initial radiotherapy followed by chemotherapy based on the CPT-SIOP-2000 protocol. A 7-month-old patient with CPC was treated with chemotherapy (CPT-SIOP-2000 protocol), while radiotherapy was deferred due to her age of less than 3 years.Multidisciplinary treatment strategies for CPC include maximal surgical resection followed by chemotherapy and radiotherapy. The CPT-SIOP-2000 study has demonstrated that the Carboplatin/Etoposide/Vincristine (CarbEV) chemotherapy protocol is effective in treating CPC.